The Risks of Relying on Artificial Intelligence (AI) as a Primary Source of Health Information (East West Medical College Journal, 2026)
As artificial intelligence becomes increasingly integrated into healthcare systems, its role as a primary source of medical information raises ethical and clinical concerns. From symptom checkers to mental health bots and many people even turn to AI as a source of first-line information. The shift, although is a forward step towards healthcare, it also carries serious risks when AI substitutes professional care rather than supplementing it. Accumulating recent empirical and review literature, this editorial examines the interconnected concerns associated with such as bias and overgeneralization, depersonalization of care, misinformation, particularly for vulnerable populations, over dependence on low-cost AI alternatives, and the potential for harm via misdiagnosis, delay of diagnosis/treatment and avoidance of professional treatment. The evidence underscores that AI must remain a tool under human oversight, not an alternative for clinicians.EWMCJ Vol. 14, No. 1, January 2026: 1-3